Leasing, Taxes, and the Cost of Capital. - Edwards, J; Mayer, C (1991)
A model of firm financial and investment behavior when there is a possibility of tax exhaustion is used to analyze the incentives for firms to act as lessees or lessors and the determination of the equilibrium rental rate in the leasing market. A number of results emerge that are relevant for public policy. It is shown that (1) leasing may diminish aggregate investment by comparison with the situation when it does not occur; (2) rents are likely to be earned on leasing activities; and (3) a purely tax-induced positive relationship exists between aggregate investment and corporate profits.